Why do not you read the label? – an integrated framework of consumer label information search. (7th July 2015) - Dörnyei, Krisztina R.; Gyulavári, Tamás
Abstract: This article facilitates deeper insight into label‐related consumer information acquisition behaviour. An integrated framework of label information search (LIS) has been developed based on a synthesis of related literature and explorative research conducted by analysing online discussions among customers (netnography). The framework focuses on three main groups of personal factors that serve as antecedents of LIS: general personal factors (e.g. health consciousness and socio‐demographics), label‐related personal factors (e.g. label‐related self‐efficacy, trust in labels and the perceived usefulness of labels) and product category‐related personal factors (trust in food products, enduring involvement, experience and perceived quality differences). Important characteristics of the framework are its process‐oriented nature and the dynamically changing relationships among its concepts. LIS is an antecedent to and a consequence of influencing factors. This article offers managerial implications and serves to incite future inquiry in this field.